Political Economic Determinants of Growth Acceleration: A Korea-Indonesia Comparative Study - Wardhana, Irwanda Wisnu (Badan kebijakan Fiskal, 2016)
This paper conducts an empirical and comparative analysis in political economy of growth acceleration determinants in Korea and Indonesia. It aims to reveal plausible explanations on Korean development success compared to Indonesia. This research provides an in-depth study parallel to a case study by using comparable variables. It examines five determinants namely initial conditions, quality of institutions, public policy innovations, socio-political circumstances, and access to external resources. The evidence exhibits Korea has better conditions in all determinants. Lesson learned from its development experiences could improve the effectiveness of the Korea official development aid.